Business Ethics in Adam Smith’s works - Zabieglik, Stefan (Annales. Etyka w Życiu Gospodarczym, 2019)
This paper presents some views of Adam Smith based on some selected problems of business ethics. These can be found in his famous works—The Theory of Moral Sentiments and The Wealth of Nations—and in his lectures at the Glasgow University, where he was a professor of moral philosophy in 1752–1764. The main argument of the paper is that ethical problems (presented mainly in The Theory of Moral Sentiments) are also present in his political economy, which contradicts some neoliberal interpretations of his works as ones of the “intellectual father of capitalism”. In The Wealth of Nations, Smith criticizes each social class because of the fact that its interests are incompatible with the good of the whole society. He condemned the monopolist efforts of the traders and entrepreneurs, described some property owners as “vain egoists” and advanced the interests of the poor. He maintained that the interests of the traders should be supported when these were compatible with the interest of the consumers. The desire for possession and wealth should be analyzed from the social point of view: It is good when it contributes to the common good and the reproduction of humankind.